Risk of psychiatric readmission in the homeless population: A 10-year follow-up study - Herrera-Imbroda, Jesús; Guzmán-Parra, José; Bordallo-Aragón, Antonio; Moreno-Küstner, Berta; Mayoral-Cleríes, Fermín (Frontiers in Psychology, 2023)
Homelessness continues to be a major social and clinical problem. The homeless population has a higher burden of disease that includes psychiatric disorders. In addition, they have a lower use of ambulatory health services and a higher use of acute care. Few investigations analyze the use of services of this population group in the long term. We analyzed the risk of psychiatric readmission of homeless individuals through survival analysis. All admission episodes to a mental health hospitalization unit in the city of Malaga, Spain, have been analyzed. Three analyses were carried out: two intermediate analyses at 30 days and one year after starting follow-up; and one final analysis at 10 years. In all cases, the event was readmission to the hospitalization unit. The aHR at 30 days, 1-year, and 10-year follow-ups were 1.387 (p = 0.027), 1.015 (p = 0.890), and 0.826 (p = 0.043) respectively. We have found an increased risk of early readmission for the homeless population and a decreased risk of readmission at 10 years. We hypothesize that this lower risk of long-term readmission may be due to the high mobility of the homeless population, its low degree of adherence to long-term mental health services, and its high mortality rate. We suggest that time-critical intervention programs in the short term could decrease the high rate of early readmission of the homeless population, and long-term interventions could link them with services and avoid its dispersion and abandonment.